Human milk donation and human milk banks: an extended typology cross-sectional study in the Chengalpattu district - Kumar, Aadithya Dileeswar; Sivakumar, Rajesh Kannan; Punniyamurthy, Manoj; Dorthy, V.; Palanisamy, Kavya (International Journal Of Community Medicine And Public Health, 2025)
Background: Human milk banks (HMBs) provide an essential service by collecting, screening, processing, and distributing donor milk, particularly for infants who cannot access their mother’s milk. Despite their importance, awareness and acceptance of HMBs remain limited in many regions. This study aims to assess the awareness, willingness, and perceived usefulness of HMBs and milk donation among reproductive-aged women in a tertiary care center in Chengalpattu district. Methods: A cross-sectional study was conducted among 230 reproductive-aged women at Chettinad Hospital and Research Institute in private medical college, a tertiary care centre in the Chengalpattu district, Tamil Nadu, India from January 2025 to March 2025 for a period of 3 months. Participants were selected using a simple random sampling method. Data were collected using a pre-tested, semi-structured questionnaire that assessed knowledge, attitudes, and perceptions regarding human milk donation and HMBs. Statistical analysis was performed using IBM-SPSS version 21.0, with significance set at p<0.05. Results: The mean participant age was 29.64 years (SD=5.78). While 79.1% had heard of milk donation, only 5.2% knew of a nearby HMB. Most acknowledged its benefits (97.4%) and were willing to donate (97.4%), citing altruism. Barriers included a lack of knowledge, kinship concerns, and logistics. Conclusions: The study reveals a strong positive attitude toward human milk donation, despite limited awareness and exposure to HMBs. Educational interventions and awareness campaigns are necessary to bridge knowledge gaps and encourage milk donation, ultimately promoting better neonatal outcomes.